1995
DOI: 10.1038/jcbfm.1995.121
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Treatment with Intravenous Basic Fibroblast Growth Factor Reduces Infarct Size following Permanent Focal Cerebral Ischemia in Rats

Abstract: Summary: Basic fibroblast growth factor (bFGF) is a polypeptide that supports the survival of brain cells (in cluding neurons, glia, and endothelia) and protects neu rons against a number qf toxins and insults in vitro. This factor is also a potent dilator of cerebral pial arterioles in vivo. In previous studies, we found that intraventricularly administered bFGF reduced infarct volume in a model of focal cerebral ischemia in rats. In the current study, bFGF (45 I-lg/kg/h) in vehicle, or vehicle alone, was in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(91 citation statements)
references
References 24 publications
3
87
0
1
Order By: Relevance
“…It increases neuronal survival, has trophic effects on brain glial and endothelial cells and is a potent systemic and cerebral vasodilator. 62,63 It has been demonstrated that administration of bFGF after permanent 64 or transient MCA occlusion 65 significantly reduced infarct volumes. Although a phase I trial in stroke patients was promising, the U.S. phase II trial was halted because patients that received bFGF did worse compared to the placebo group, and the companion European trial failed to show efficacy.…”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…It increases neuronal survival, has trophic effects on brain glial and endothelial cells and is a potent systemic and cerebral vasodilator. 62,63 It has been demonstrated that administration of bFGF after permanent 64 or transient MCA occlusion 65 significantly reduced infarct volumes. Although a phase I trial in stroke patients was promising, the U.S. phase II trial was halted because patients that received bFGF did worse compared to the placebo group, and the companion European trial failed to show efficacy.…”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…53−55 In animal models (rat and cat), early administration (less than 1 to 3 h, iv infusion) reduced the infarct volumes in the MCAO side of the cerebral hemisphere. 10,13,56 On the other hand, delayed treatment with bFGF (started 1 day postinfarct, intracisternally) in the MCAO rat model did not ameliorate the cerebral infarct volumes but resulted in an enhancement of the recovery of the cerebral motor functions of the contralateral limbs in cases of prolonged survival.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The highly discriminatory and selective BBB is relatively impermeable to compounds with M r greater than 400-500 daltons. 38,39) In the suture-occlusion model of MCA in rats, BBB disruption was reported to occur 2-4 h after occlusion, 40) leading to vasogenic cerebral edema. On the other hand, BBB disruption enables large molecules to enter the brain.…”
Section: Discussionmentioning
confidence: 99%